Clinical Variables Associated With Statural Growth in Pediatric Crohn's Disease Differ by Sex (The Growth Study). Issue 6 (29th August 2020) - Gupta, Neera; Lustig, Robert H; Andrews, Howard; Gokhale, Ranjana; Goyal, Alka; Patel, Ashish S; Guthery, Stephen; Sylvester, Francisco; Siebold, Leah; Leu, Cheng-Shiun
Abstract: Background: Statural growth impairment is more common in male patients with Crohn's disease (CD). We identified clinical variables associated with height z score differences by sex in children participating in the Growth Study, a prospective multicenter longitudinal study examining sex differences in growth impairment in pediatric CD. Methods: Patients with CD (female patients with bone age [BA] ≥4 years 2 months and ≤12 years; male patients with BA ≥5 years and ≤14 years at screening) who had completed study visit 1 qualified. The height z score difference was computed as height z score based on chronological age minus height z score based on BA. Results: One hundred thirteen patients with CD (36% female) qualified. The mean chronological age was 12.0 ± 1.8 (SD) years. The magnitude of the mean height z score difference was significantly greater in female patients (–0.9 ± 0.8) than in male patients (–0.5 ± 0.9; P = 0.021). An initial classification of inflammatory bowel disease as CD ( P = 0.038) and perianal disease behavior at diagnosis ( P = 0.009) were associated with higher standardized height gain with BA progression, and arthralgia at symptom onset ( P = 0.016), azathioprine/6-merpcaptopurine ( P = 0.041), and probiotics ( P ≤ 0.021) were associated with lower standardized height gain with BA progression in female patients. Patient-reported poor growth at symptom onset ( P = 0.001), infliximab ( P ≤ 0.025), biologics ( P ≤ 0.015), methotrexate ( P = 0.042), and vitamin D ( P ≤ 0.010) were associated with higher standardized height gain with BA progression, and initial classification as CD ( P = 0.025) and anorexia ( P = 0.005) or mouth sores ( P = 0.004) at symptom onset were associated with lower standardized height gain with BA progression in male patients. Conclusions: Different clinical variables were associated with statural growth in male patients vs female patients, suggesting that sex-specific molecular pathways lead to statural growth impairment in CD.